Nanoclay composites in electrochemical sensors - Timakwe, Sapokazi; Ngcobo, Sizwe; Smith, Randall; Matoetoe, Mangaka (Frontiers in Sensors, 2024)
Nanoclays are layered structures in the nano-scale range with wide spread application as a result of their unique properties such as swelling, cation exchange capacity and ease of functionalisation using metals, metal oxides, organic compounds such as carbon paste, polymers and other biomolecules forming nanoclay composites. The nanoclay functionalisation with silver (Ag), zinc oxide (ZnO), and bimetallic silver-gold (Ag-Au) using a hydrophilic and hydrophobic clays was evaluated discussed.The composites synthesis, morphological, crystallinity and electroactivity properties in comparison with the pure nanoclay was assessed. All these nanoclay composites layered structure and crystallinity were slightly changed. Nanocomposites clumped layered structures surface had dispersed white spots indicating possible surface modification. Comparatively the nano films of composites electroactivity was high as seen from current increase in Cyclic voltammetry characterisation voltammograms and the differential pulse voltammograms of the pharmaceutical detection. The efavirenz, nevirapine, and zidovudine detection was improved by Human serum albumin (HSA)modification of the nanocomposite , as shown by higher current. Thus, indicating improved conductivity of the composites compared to the pure nanoclays. Application of HSA modified nanocomposites in analysis of efavirenz, nevirapine, and zidovudine on glassy carbon electrode (GCE) showed good linearity and acceptable detection limits comparable to previous studies. Therefore has a potential for application in pharmaceutical quality control and environmental monitoring.